Modeling the relationships between perceptions about technology and attitudes toward computers - Khine, Myint Swe; Afari, E. (2014)
Over the past few years, the relationship between attitudes and behavior has been of a major interest to educators. Previous studies have found varying degree of associations between attitudes, behavioral intention and perceptions and corroborate the fact that attitudes influence patterns of behavior. As computer technology is becoming pervasive in the society, researchers have attempted to explore the links between individual's perceived ease of use, perceived usefulness and their intention to use the computer technology. A study was conducted in two higher education institution in the United Arab Emirates to find out students' intention to use computer technology employing the Technology Acceptance Model (TAM) by Reference [1] as a theoretical framework and Structural Equation Modeling as an analytical tool. The results revealed strong relationships between the students' attitudes toward computer and intention to use. This paper further reports the applicability of technology acceptance model and its robustness and generalizability in different research contexts.